TRADITIONS AND INNOVATIONS IN JADE CARVING IN CHINESE CULTURE - Тан, Чжунянь; Пашкевич, К. Л. (Art and Design, 2023)
The aim of the article is to analyze the features of jade and its varieties, the variety of uses from ancient times to the present, the art of jade as a historical and cultural phenomenon of China and the world. Methodology. The research methodology is determined by a comprehensive study of the subject and includes: methods of analysis, synthesis, induction, comparison, method of structural and systemic analysis of sources, historical, linguistic, comparative and experimental method. Historical, cultural, and art history scientific approaches combined with comparative and presentational methods are applied. Results. The degree of study of the topic in professional literature, in particular scientific literature by Chinese authors, is determined. The main properties of jade are indicated, the features of jade processing are analyzed, and examples of jade products are given. features and history of jade processing in China. The analysis covers the historical-material aspect of Chinese jade artifacts and works of art, examples are given. The peculiarities of using natural motifs in jade jewelry are considered. The works of modern masters with jade are analyzed. Scientific novelty. The scientific novelty of the study consists in the comprehensive study of the topical, little-researched topic dedicated to the jade art of China, and covers the historical and material aspects of Chinese jade artifacts and works of art. Practical significance. The materials of the article can be used when studying the topic of design in higher education and when writing scientific papers.